Environmental impact assessment in Metropolitan Cebu, Philippines : issues and challenges - Muego, Andres Evangelista; Zimmerman, Willi; Nurul Amin, A.T.M.; Frankel, Richard J.; Nguyen Kim Oanh; Funds for Assistance to Private Education (PAPE, Phils.); Canadian International Development Agency (CIDA); Canadian Universities Consortium (CUC) (Bangkok : Asian Institute of Technology, 1999)
This study identifies key issues in the Environmental Impact Assessment (otherwise known as Philippine Environmental Impact Statement) system in Metro Cebu, in determining major challenges and strategies towards its' effective implementation. The key issues were identified through the 'delphi exercise.' Case studies of two Environmental Impact Statements (EIS) and one Initial Environmental Examination (IEE) projects were undertaken in gaining insights into the system's implementation, and in determining the strengths and weaknesses of the Dept. Administrative Order No. 96-37. The Strengths, Weaknesses, Opportunities and Threats (SWOT) analysis determined the strategies addressing EIA issues. Several issues were being identified, among others: project proponents lack of EIA appreciation; a pro-development political culture; the project proponents' treatment of EIA as bureaucratic requirement; non-implementation of Environmental Compliance Certificate conditions; etc. Addressing these issues, a number of strategies are suggested. Foremost, is the need "to continuously conduct education, training programs and courses to government authorities, EIA practitioners, EIA review committee, policy-decision makers, Non Government Organizations (NGOs), public/community, and project proponents. The desired ultimate effect of EIA is in influencing Metro Cebu's sustainability. Towards this end, the major challenge is the "internalization of EIA procedures in planning and decision-making." However, procedural · improvements alone will not contribute significantly towards the internalization of EIA procedures, unless the 'preconditions [e.g. environmental awareness, political culture, etc]' for effective EIA is addressed. The study recommended the consideration of a model for multi-dimensional system approach to enhance the effectiveness of EIA System implementation in Metro Cebu.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science. School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1999
Keywords: Environmental impact analysis -- Philippines -- Cebu